Cardiac-Specific Bdh1 Overexpression Ameliorates Oxidative Stress and Cardiac Remodeling in Pressure Overload–Induced Heart Failure. (December 2017) - Uchihashi, Motoki; Hoshino, Atsushi; Okawa, Yoshifumi; Ariyoshi, Makoto; Kaimoto, Satoshi; Tateishi, Shuhei; Ono, Kazunori; Yamanaka, Ryoetsu; Hato, Daichi; Fushimura, Yohei; Honda, Sakiko; Fukai, Kuniyoshi; et al.
Abstract : Background: Energy starvation and the shift of energy substrate from fatty acids to glucose is the hallmark of metabolic remodeling during heart failure progression. However, ketone body metabolism in the failing heart has not been fully investigated. Methods and Results: Microarray data analysis and mitochondrial isobaric tags for relative and absolute quantification proteomics revealed that the expression of D-β-hydroxybutyrate dehydrogenase I (Bdh1), an enzyme that catalyzes the NAD + /NADH coupled interconversion of acetoacetate and β-hydroxybutyrate, was increased 2.5- and 2.8-fold, respectively, in the heart after transverse aortic constriction. In addition, ketone body oxidation was upregulated 2.2-fold in transverse aortic constriction hearts, as determined by the amount of 14 CO2 released from the metabolism of [1- 14 C] β-hydroxybutyrate in isolated perfused hearts. To investigate the significance of this augmented ketone body oxidation, we generated heart-specific Bdh1-overexpressing transgenic mice to recapitulate the observed increase in basal ketone body oxidation. Bdh1 transgenic mice showed a 1.7-fold increase in ketone body oxidation but did not exhibit any differences in other baseline characteristics. When subjected to transverse aortic constriction, Bdh1 transgenic mice were resistant to fibrosis, contractile dysfunction, and oxidative damage, as determined by the immunochemical detection of carbonylated proteins and histone acetylation. Upregulation of Bdh1 enhanced antioxidant enzyme expression. In our in vitro study, flow cytometry revealed that rotenone-induced reactive oxygen species production was decreased by adenovirus-mediated Bdh1 overexpression. Furthermore, hydrogen peroxide–induced apoptosis was attenuated by Bdh1 overexpression. Conclusions: We demonstrated that ketone body oxidation increased in failing hearts, and increased ketone body utilization decreased oxidative stress and protected against heart failure. Abstract : Supplemental Digital Content is available in the text.